Steel weight saving developed from semi-continuous construction in multi-storey braced steel frame based on euro-code 3 - Taher, T. Y. (Penerbit UTM Press, 2015)
Steel frames can be designed as simple, semi-continuous, and continuous construction. However, these types of constructions depend on the type of connections used. Connections are usually classified in design as pinned which is associated with simple construction or rigid which is associated with continuous construction. However, the actual behaviour in most cases is classified as semi-rigid connections or partial strength. The semi-rigid connections usually associated with the stiffness of the connection while the strength of this connection usually associated with partial strength. The use of semi-rigid connection has been encouraged by Euro-code 3 and studies on the matter known as semi-continuous construction have proven that substantial savings in steel weight of the overall construction. A series of parametric studies on two bays of two, four, six, and eight storey of multi-storey braced steel frame are presented in this paper. All frames are designed using S275 steel and flush end-plate connection was used as connection for semi-continuous construction whereas fin plate connection was used for simple construction. The frames are designed both as simple construction and semi-continuous construction and the steel weight of the frames was calculated and compared. From the parametric study it was found that by using partial strength connection the saving in steel weight of the frames is in the range of 11.5% to 22.5% of the total steel weight of the frames.